Pendampingan Pembuatan Jamu sebagai Produk Inovatif Desa Gunung Raja - M Hasbiansyah Putra Wibisono; Farisi Fardiansyah; Nova Fitriyanti; Ine Nadilla Vinka Putri; Ayu Nadiah; sopian sopian (JURNAL PENGABDIAN KADER BANGSA, 2025)
Jamu is a traditional medicine that is an important component of Indonesian culture, particularly in Gunung Raja Village. This Community Service project aims to examine the potential of jamu as an innovative product capable of improving the welfare of rural communities. This Community Service project uses qualitative methods to identify the types of jamu produced, their production processes, and the social and economic impacts of jamu product development in Gunung Raja Village. The results of the Community Service project show that jamu functions both as medicine and a source of income for the community, while also contributing to the preservation of local culture.